Impact of Motivation on the Speaking Skills of the ESL Learners: A Study Conducted at intermediate level in Rahim Yar Khan - Anwar, Hina; Zahid, Zohaib; Ilyas, Sitara (Annals of Human and Social Sciences, 2025)
This study examines the various forms of institutional motivation for ESL students and pinpoints the elements that drive them during the learning process. Involving college students at an intermediate level, this descriptive study uses both a quantitative and qualitative design. Both open-ended and closed-ended questionnaires were used to gather data from EFL students. This research identifies the motivating elements. The research revealed that in this particular context, students' ESL learning process is significantly influenced by both instrumental and integrative motivation. His research did, however, show that instrumental motivation played a major part in ESL instruction. Additionally, according to Williams and Burden, the data indicated that thirteen factors influenced the students' learning. The various theories of institutional motivation are defined in this study at an intermediate level. This study used a quantitative research design in order to describe and systematically explore the phenomena being studied. A structured Copa OK as a Foreign Language Learner questionnaire was used in the study to collect data from her family. Open-ended and closed-ended questionnaires were used to collect the data, which were presented in both quantitative and qualitative form. The statistical package for the social sciences (SPSS) software was used to quantitatively analyze the gathered data, providing insightful statistical analysis and solid results.